Stress Levels Determine Migraine Incidence in Medical Students of Duta Wacana Christian University - Jonathan Dave; Esdras Ardi Pramudita; Rizaldy Taslim Pinzon (Universitas Airlangga, 2022)
Highlight: Stress can trigger migraine. There is a significant relationship between stress levels and the occurence of migraine The higher the stress level, the higher the risk of migraine ABSTRACT Introduction: Migraine is the second most common primary headache after tension-type headache. Stress is one of the factors that can contribute to migraine occurrence. Medical students are subjected to a high-stress level due to their educational program, which increases their risk of migraine. Objective: To measure the relationship between stress levels and migraine occurrence in medical students of Duta Wacana Christian University, batch 2020. Methods: This study used an observational analytical design with a cross-sectional method and involved 61 respondents from the medical students of Duta Wacana Christian University, batch 2020, who met the inclusion and exclusion criteria. Respondents were required to approve informed consent and complete the Perceived Stress Scale and Migraine Screen Questionnaire before conducting the research. Results: The Chi-Square for Trend statistical analysis for trends showed that stress levels were related to migraine (p < 0.05), age variables revealed no association with migraine (p > 0.05), and gender revealed that the sexes had a relationship with migraine (p < 0.05). Using Fisher's statistical technique, this study found that menstrual status has no association with migraine (p > 0.05). Conclusion: Stress levels and migraine frequency were significantly correlated, meaning that high-stress levels can trigger migraines.